ANALISIS UPAYA PENCEGAHAN SWABAKAR PADA STOCKPILE RL 56 TAMBANG AIR LAYA PT BUKIT ASAM, Tbk. TANJUNG ENIM - Elsy Sonia Lukalma Putri; Suhardiman Gumanti; Dedi Yansen (Pojok Publisher, 2025)
Coal is one of the main energy sources in Indonesia, often temporarily stored in stockpiles before distribution. However, this storage is susceptible to self-combustion, a spontaneous combustion process caused by coal oxidation reactions that result in increased temperatures. Self-combustion in stockpiles can reduce coal quality and cause company losses. One location that experienced this is Left Stock RL 56, a coal stockpile of AL 71 at the Air Laya Mine of PT Bukit Asam, Tbk. This study aims to analyze the factors causing self-combustion and efforts to address and prevent it. The methods used include field observation, collection of primary and secondary data such as coal temperature data, stockpile dimensions, stockpiling patterns, rainfall data, and coal quality, which are then analyzed. The results show that self-combustion at the study location was triggered by several main factors, namely the long stockpiling period (approximately ± 5 months), the lack of an optimal FIFO system, stockpiling heights reaching 11 meters, and significant increases in coal temperature at several measurement points. The stockpiling pattern used has also not consistently adopted a system that can minimize the risk of self-combustion. Recommended preventative measures include proper stockpile management, regular temperature monitoring, the FIFO system, and immediate handling using heavy equipment when temperatures are detected high. By improving stockpile management systems, the potential for future fires can be minimized.